Kedudukan Hukum Deponeering dalam Sistem Peradilan Pidana - Desi Ratnasari; Sahuri Lasmadi; Elly Sudarti (PAMPAS: Journal of Criminal Law, 2021)
This article aims to identify and analyze the legal implications and analyze the regulation of public interest as a condition for implementing deponeering by the Attorney General for the sake of the public interest in the perspective of the development of criminal procedural law. This research is a legal research, obtained from statutory studies (statute approach), concept (conceptual approach), cases. The result of this research is that there is discrimination against equality before the law contained in Article 27 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia and can trigger misinterpretation by the Attorney General. Then in its implementation there is no clear regulation regarding the application of the opportunity principle related to the authority of the attorney general in the implementation of case waiver (deponeering) for the public interest in the Criminal Procedure Code.Â  Abstrak Artikel ini bertujuan untuk mengetahui dan menganalisis implikasi hukum serta menganalisis terhadap regulasi kepentingan umum sebagai syarat pelaksanaan pengesampingan perkara (deponeering) oleh Jaksa Agung demi kepentingan umum dalam prespektif perkembangan hukum acara pidana.Â  Penelitian ini merupakan penelitian hukum, yang diperoleh dari studi perundang-undangan (statute approach), konsep (conceptual approach), kasus. Hasil dari penelitian ini adalah adanya diskriminatif terhadap equality before the law yang terdapat dalam Pasal 27 Ayat (1) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan dapat memicu salah tafsir oleh Jaksa Agung. Lalu di dalam pelaksanaannya belum terdapat regulasi yang jelas mengenai penerapan asas oportunitas yang berhubungan dengan kewenangan jaksa agung dalam pelaksanaan pengesampingan perkara (deponeering) demi kepentingan umum di dalam Kitab Undang-Undang Hukum acara Pidana (KUHAP).Â